Objective measures of sleep duration and continuity in major depressive disorder with comorbid hypersomnolence: a primary investigation with contiguous systematic review and meta‐analysis. (1st February 2017) - Plante, David T.; Cook, Jesse D.; Goldstein, Michael R.
Summary: Hypersomnolence plays an important role in the presentation, treatment and course of mood disorders. However, there has been relatively little research that examines objective measures of sleep duration and continuity in patients with depression and hypersomnolence, despite the use of these factors in sleep medicine nosological systems. This study compared total sleep time and efficiency measured by naturalistic actigraphic recordings followed by ad libitum polysomnography (PSG; without prescribed wake time) in 22 patients with major depressive disorder and co‐occurring hypersomnolence against age‐ and sex‐matched healthy sleeper controls. The major depressive disorder and co‐occurring hypersomnolence group demonstrated significantly longer sleep duration compared with healthy sleeper controls quantified by sleep diaries, actigraphy and ad libitum PSG. No between‐group differences in sleep efficiency (SE), latency to sleep or wake after sleep onset were observed when assessed using objective measures. To further contextualize these findings within the broader scientific literature, a systematic review was performed to identify other comparable investigations. A meta‐analysis of pooled data demonstrated patients with mood disorders and co‐occurring hypersomnolence have significantly greater sleep duration and similar SE compared with healthy controls when assessed using ad libitum PSG. These results suggest current sleep medicine nosology that distinguishes hypersomnia associated with psychiatric disorders primarily as a construct characterized by low SE and increased time in bed may not be accurate. Future studies that establish the biological bases hypersomnolence in mood disorders, as well as clarify the accuracy of nosological thresholds to define excessive sleep duration, are needed to refine the diagnosis and treatment of these disorders.